Stormbreaker - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2006)
After the death of the uncle who had been his guardian, fourteen-year-old Alex Rider is coerced into continuing his uncle's dangerous work for Britain's intelligence agency, MI6.